Effect of In Situ Gelatin Addition on Synthesis and Characteristics of Limestone Based Hydroxyapatite using Sol-Gel Method - Luluk Edahwati; Nazila Alfi Rahmah; Mohammad Rafli Alif Wahyudi (TEKNIK, 2025)
Hydroxyapatite (HAp) is a major component of bone and tooth tissues used to repair and rebuild malfunctioning bone. Hydroxyapatite synthesis widely utilizes materials that have a high calcium content. In this study, limestone was used as an economical calcium precursor. Gelatin was added in situ during the sol-gel process to improve biomechanical properties such as porosity and reduce 5the particle size. The variables used during hydroxyapatite synthesis were gelatin concentrations of 30%, 40% and 50% with pH variations of 10, 11 and 12. The best yield was 30% gelatin concentration with pH 12. HAp products were characterized using Fourier Transform Infra-Red (FTIR) to confirm that there are core functional groups that compose hydroxyapatite, namely PO43-, CO(3)(2-)and OH-. SEM-EDX analysis revealed granular crystal morphology with particle dimensions below 600 nm and the highest porosity of 60.73% at pH 10. These results indicate that the in situ addition of gelatin during the sol-gel process successfully produced hydroxyapatite with biomechanical properties suitable for implant applications, especially in teeth, with optimal porosity and adequate particle size to support cell growth.